2009
DOI: 10.1111/j.1399-3046.2008.01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirusinfection in children who underwent hematopoietic stem cell transplantation at a single center: A retrospective study of the risk factors

Abstract: CMV infection is one of the major causes of morbidity and mortality after HSCT. The aim of this single center retrospective study was to analyze risk factors for CMV infection in pediatric patients who underwent HSCT. We retrospectively reviewed the medical records of 117 pediatric patients who underwent allogeneic HSCT at Asan Medical Center between December 2000 and January 2007. After HSCT, CMV antigenemia was detected by identifying CMV pp65 early antigen in white blood cells. The incidence of CMV antigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
31
5
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 29 publications
12
31
5
7
Order By: Relevance
“…Alemtuzumab was further associated with a tendency toward an earlier onset of CMV infection compared to patients receiving ATG or no in vivo TCD. Previous reports indicated that in vivo TCD with either ATG or alemtuzumab enhanced the CMV infection risk [15][16][17]. Our analysis including a direct comparison of both approaches revealed that ATG and alemtuzumab differentially influence the CMV infection risk, albeit that this hypothesis should be reevaluated in a larger patient cohort.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Alemtuzumab was further associated with a tendency toward an earlier onset of CMV infection compared to patients receiving ATG or no in vivo TCD. Previous reports indicated that in vivo TCD with either ATG or alemtuzumab enhanced the CMV infection risk [15][16][17]. Our analysis including a direct comparison of both approaches revealed that ATG and alemtuzumab differentially influence the CMV infection risk, albeit that this hypothesis should be reevaluated in a larger patient cohort.…”
Section: Discussioncontrasting
confidence: 45%
“…Moreover, CMV-seropositive unrelated donor stem cell recipients with a CMV-seronegative donor are reported to have a significantly higher treatment-related mortality and lower 5-year survival than those with a CMV-seropositive donor, though the impact of the donor's CMV serostatus is still controversially discussed [10,11]. Further risk factors for CMV infection and/or disease in patients after allo-SCT might include the use of in vitro or in vivo T cell depletion (TCD) with agents such as antithymocyte globulin (ATG) or alemtuzumab, GvHD prophylaxis with mycophenolate mofetil (MMF), the recipient's female sex, the use of a matched unrelated donor and the recipient's age [9,[12][13][14][15][16][17]. Three months after allo-SCT, a CD4 ?…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for CMV infection in HSCT patients include CMV seropositivity of donor and recipient, allogeneic transplantation (especially with T cell-depleted unrelated or HLA-mismatched donors) and cell source. Cord blood recipients have both longer and higher cumulative incidences of CMV infection compared to peripheral blood or allogeneic bone marrow recipients from related or unrelated donor origin (Keever-Taylor et al, 2001;Yoon et al, 2009;Yi and Kim, 2012). In HSCT patients, cellular immunity is mainly significantly impaired during the first 100 days post-transplant.…”
Section: Introductionmentioning
confidence: 99%
“…Данная корреляция описана во многих работах и, вероятно, связана с вли-янием системной иммуносупрессии при острой РТПХ на механизмы врожденного или остаточного перене-сенного ЦМВ-специфичного иммунитета [13,35,36]. Нами продемонстрировано, что пациенты со злокаче-ственными заболеваниями имеют более высокий риск реактивации ЦМВ-инфекции по сравнению с пациен-тами с незлокачественными заболеваниями, о чем свидетельствует результат мультивариантного ана-лиза.…”
Section: обсуждение результатов исследованияunclassified
“…В моно-и мультива-риантных анализах получено значимое влияние на риск ЦМВ-виремии, предшествующей острой РТПХ > II стадии, серопозитивности реципиента до ТГСК и наличия у пациента злокачественного заболевания. КВ ЭБВ-инфекции -33% (95% ДИ [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Фактором риска ЭБВ-виремии являлась острая РТПХ > II стадии.…”
unclassified